Intelligent Decision Scheme of Ordered Power Consumption Based on Fish Swarm Algorithm Optimization - Sui, Bing; Yu, Peng; Shou, Zeng; Bao, Anning; Liu, Qi; Zhao, Quanxin (2024 9th Asia Conference on Power and Electrical Engineering (ACPEE), 2024)
In this paper, an intelligent decision scheme for a fish swarm algorithm is presented. The fish swarm algorithm in the scheme is applied on optimizing power consumption in power system to reduce energy consumption and improve energy efficiency. By applying the fish swarm algorithm to appraise and optimizes the power consumption of the power system, and to finding the optimal power consumption decision in complex environment, the scheme effectively relieves the pressure of the power system, and reduces energy waste.